2017
DOI: 10.1039/c6an02532c
|View full text |Cite
|
Sign up to set email alerts
|

Structural and elemental changes in glioblastoma cells in situ: complementary imaging with high resolution visible light- and X-ray microscopy

Abstract: The glioblastoma (GBM) is characterized by a short median survival and an almost 100% tumor related mortality. GBM cells exhibit highly invasive behavior whose mechanisms are not yet fully understood. The present study explores application of X-ray and visible light microscopy to display the elemental and structural images of cells from 3 patient derived GMB samples and an established GMB cell line. Slight differences in elemental concentrations, in actin cytoskeleton organization and cell morphology were note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…GBM may develop de novo (the primary tumor) or via malignant progression from lower-grade glioma (LGG) as glioblastoma IDH mutated [3]-regardless of derivation, patient's prognosis is dismal [4]. The malignant phenotype of GBM results from, e.g., dynamics of cytoskeleton [5,6], which has been found to guide signaling pathways [7], proliferation [8], polarity [9], cell cycle [10], or epithelial-to-mesenchymal transition (EMT) [11] and metastasis [12]. Ultimately, cytoskeleton controls two processes that impact on cancer malignant behavior, i.e., cellular division and invasion [6].…”
Section: Introductionmentioning
confidence: 99%
“…GBM may develop de novo (the primary tumor) or via malignant progression from lower-grade glioma (LGG) as glioblastoma IDH mutated [3]-regardless of derivation, patient's prognosis is dismal [4]. The malignant phenotype of GBM results from, e.g., dynamics of cytoskeleton [5,6], which has been found to guide signaling pathways [7], proliferation [8], polarity [9], cell cycle [10], or epithelial-to-mesenchymal transition (EMT) [11] and metastasis [12]. Ultimately, cytoskeleton controls two processes that impact on cancer malignant behavior, i.e., cellular division and invasion [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to obtain information regarding the subcellular distribution of redox-active trace elements Cu and Fe, as well as Zn, we employed the XRF microscopy at the APS synchrotron facility. The XRF microscope installed on the Bionanoprobe bio-imaging stations provided the sample orientation necessary for this correlative imaging and high spatial and chemical resolution for hard X-ray imaging of single cells [34]. Moreover, the online visible light microscope provided better precision than a micrometer for the positioning of investigated cells.…”
Section: Resultsmentioning
confidence: 99%
“…29,36,37 Besides, we showed that elemental composition and cytoskeletal structure differ in the same patient-derived GBM cells, as studied by synchrotron radiation-based soft-X-ray tomography and hard X-ray fluorescence. 35 Thus, as a step forward, in this study, we first synthesized characterized and afterward tested a system based on carbon nanoparticles from the 2-acrylamido-2-methylpropanesulfonic acid (AMPS), as a possible organic delivery system (AMPS-CDs NPs), for the drug riluzole in GBM cells. We chose AMPS as a potential nanocarrier, as it possesses free sulphonyl, carboxyl, and amide groups.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, riluzole directly affects biomacromolecule changes, namely, carbohydrate metabolism, DNA structure, lipid structures, and protein secondary conformation. 28 Riluzole is approved by the Food and Drug Administration (FDA) as an amyotrophic lateral sclerosis (ALS) drug, 29 and recent studies showed that treatment with riluzole suppresses the proliferation of many cancer cells 30 35 and GBM. 29 , 36 , 37 Besides, we showed that elemental composition and cytoskeletal structure differ in the same patient-derived GBM cells, as studied by synchrotron radiation-based soft-X-ray tomography and hard X-ray fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation